RESPON PENAWARAN PETANI BAWANG PUTIH DI TENGAH PANDEMI COVID-19 - Ahmad Zainuddin; Intan Kartika Setyawati; Illia Seldon Magfiroh; Rena Yunita Rahman; Dudi Septiadi (Universitas Sebelas Maret, 2022)
Garlic is one of the main staples contributing to the biggest inflation in Indonesia because domestic prices tend to increase. On the other hand, imports of Indonesian garlic have an increasing trend even during the Covid-19 pandemic. This will certainly affect the supply of garlic farmers. The purpose of this study was to determine the response of garlic farmers to changes in domestic and import prices during the Covid-19 pandemic. This study was used secondary data in the form of annual time series data with a period of 30 series, from 1990 to 2020. In this study, an attempt has been made to examine the supply response of garlic farmers in Indonesia by using Error Correction Model (ECM). The results showed that the Covid-19 pandemic caused garlic farmers to be very responsive to domestic prices, but not responsive to import prices. Therefore, high prices are also an incentive for farmers to increase their income of garlic farmers.